(3GdJHjGf aj Yde GdHjGf GdeWdY Ydi EYLGR GdbQBfs - (3YHO GdhGMO Hf YHO GdcQje Hf Nda GdCfUGQj GdRedcGfj, CHh GdecGQe, ceGd GdOjf, hjbGd dg GHf NWjH RedcG,J (B651 (3g` s ((3eMeO Hf SYjO Hf eMeO GdQYjfi s)
(3ChdgG (B:s
( (3GdMeOddg GdPi CfWb CdSfI GdCbdGe HEMcGe GdCMcGe (B) (3Ke PcQ Yde GdHjGf hCf GdeUfaGJ ajg bdjd , hCLeYgG OdGFd GdEYLGR dYHO GdbGgQ GdLQLGfi Ke YbH Ydjg Hbhdg (B: " (3ZjQ Cfg hGSY GdNWh s
(3BNQgG (B:s
(3hdbO EfJgjfG Edi ZGjI GdJMbjb hEdi Gddg GdcQje CHJgd Cf jLYd LedJg fGWbkG HNGJeJg ai SjQg hYdGfjJg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B209s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B341s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs